2021
DOI: 10.1038/s41598-021-98974-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the thermal conductivity of multilayer graphene by strain

Abstract: Straintronics is a new concept to enhance electronic device performances by strain for next-generation information sensors and energy-saving technologies. The lattice deformation in graphene can modulate the thermal conductivity because phonons are the main heat carriers. However, the device fabrication process affects graphene’s heat transport properties due to its high stretchability. This study experimentally investigates the change in the thermal conductivity when biaxial tensile strain is applied to graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This indicates that alloying can cause local lattice distortion within the material. Generally, the vibrational properties of materials on account of thermal fluctuations will be impacted significantly if the crystal microstructure is changed by means of strain or physical modulation, and thus the thermal properties will be affected by it.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that alloying can cause local lattice distortion within the material. Generally, the vibrational properties of materials on account of thermal fluctuations will be impacted significantly if the crystal microstructure is changed by means of strain or physical modulation, and thus the thermal properties will be affected by it.…”
Section: Resultsmentioning
confidence: 99%
“…For graphene, many studies demonstrated that the κ value of graphene decreases monotonically under tensile strain. 276,277 However, others have shown that the κ value of graphene increases with increasing tensile strain, in contrast to the flexural modes. 278 And even more, it is also found that tensile strain can reduce or enhance the κ value of graphene, depending on the size of the sample.…”
Section: Non-structure Engineeringmentioning
confidence: 99%
“…[5][6][7] Likewise, the design of phononic devices capable of performing logic operations with phonons, analogous to what their electronic counterparts do with charge carriers, may also be envisaged on the basis of the concept of active κ control. 8,9 Such a technological goal can be achieved, for instance, via strain 10 and chemical intercalation 11 in layered materials. However, these approaches appear to be rather impractical due to their long response times and complex setups.…”
Section: Introductionmentioning
confidence: 99%